Análise espacial do perfil dos nascidos vivos no município de Belo Horizonte em 2000, com foco naqueles potencialmente vulneráveis ao óbito infantil - Vanessa Lima Caldeira Franceschini (2008)
In the present study clustering of incidence of vulnerable live births for the city of Belo Horizonte, 2000 were done. The aim was to verify whether spatial patterns in the distribution of live births in the city existed and whether they were related to specific socioeconomic conditions. In order to accomplish this task, indexes of Moran (Global and Local) were applied to estimate spatial autocorrelation between pairs of neighbors, weighted by proximity. Data used were from the National System of Live Births (SINASC). Information has been obtained in the individual level and afterwards, grouped by areas of coverage of 145 health centers and 9 health districts. Thus, the inferences are valid in aggregate level (ecological study). Variables studied were selected based on literature review and information availability and qualifty. Of the 38.623 live births 6.113 cases were eliminated for which it was not possible to decide to which cluster they belong (68) or there was no information on any of the selected variables (6.045). Data used in producing the indicators for attainment of descriptive analysis of the characteristics of live births were processed in SPSS software (version 13.0) and the clustering maps were done in MapInfo software (version 7.5). The main results are that in almost all health districts, more vulnerable clusters for infant mortality were in areas marked by the presence of villages/slums or housing. These areas had low average and median income and low quality of urban life. The exception was the health districts Nordeste and Pampulha, that did not show clustering of vulnerability groups.